The Union Power During the Social Outburst in Chile. the General Strike in November 2019 - Osorio-Lavín, S (FED ESPANOLA SOCIOLOGIA, 2022)
The protest wave in October 2019 in Chile has been described as a spontaneous and unorganized event. However, an in-depth analysis shows the active participation of trade unions. To understand the specific unionism s role in the revolt, this research investigate how power resources deployment impacted on the force that the general strike had on the political arena. Results suggest that the strike success was based on associative resource, which allowed an extraordinary participation of workers from different economic sectors; and societal resource, that allowed a massive protest through the alliance with other social actors, generating a pressure which forces the political system to open a constituent process, and reaffirming the relevance of trade unionism and the strike as the main protest tactic in a social mobilization context.